A novel polymer quantum dot derived from poly(3,4-ethylenedioxythiophene) and its application for sensing and optical imaging - Xu, Qian (2014)
The conventional commercially available flurophores play a significant role in complex and dynamic biological processes these years. However, they suffer from several intrinsic drawbacks like rapid photo-bleaching making it difficult to carry out long-term imaging. Semiconductor quantum dots (semi-QDs) have been regarded as alternatives, but they may possess some limitations, including cytotoxicity, carcinogenicity, and too-large size. Alternatively, the novel quantum dots derived from polymers possess certain advantages such as superior photo-stability, high biocompatibility, small size and tunable optical properties, thereby, promising them as superior substitutes for semiconductor QDs.